2022
DOI: 10.1021/acsomega.2c04212
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Prognosis Model of the Pyroptosis-Related Gene in Multiple Myeloma and Screening of Core Genes

Abstract: Pyroptosis is an important factor affecting the proliferation, invasion, and metastasis of tumor cells. However, in multiple myeloma (MM), there are few studies on whether the occurrence of pyroptosis is related to the occurrence and prognosis of the disease. Based on the Gene Expression Omnibus and Cancer Genome Atlas database search dataset, this study identified pyroptosis-related genes with a specific prognosis, constructed and verified the prediction model by stepwise Cox regression analysis and time rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 48 publications
0
7
2
Order By: Relevance
“…The immune infiltration analysis revealed that the infiltration degrees of many immune cells were different in cluster 1 and cluster 2, which indicates the composition of the immunological microenvironment may affect the prognosis of myeloma. Li et al [ 13 ] also performed a clustering analysis based on the TCGA-MMRF database and identified two clusters using the R package “ConsensusClusterPlus”. Similar to the findings of our study, their study showed that the levels of immune activation were different in two clusters, indicating that pyroptosis could be involved in defining the immunological microenvironment of MM [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The immune infiltration analysis revealed that the infiltration degrees of many immune cells were different in cluster 1 and cluster 2, which indicates the composition of the immunological microenvironment may affect the prognosis of myeloma. Li et al [ 13 ] also performed a clustering analysis based on the TCGA-MMRF database and identified two clusters using the R package “ConsensusClusterPlus”. Similar to the findings of our study, their study showed that the levels of immune activation were different in two clusters, indicating that pyroptosis could be involved in defining the immunological microenvironment of MM [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 13 ] also performed a clustering analysis based on the TCGA-MMRF database and identified two clusters using the R package “ConsensusClusterPlus”. Similar to the findings of our study, their study showed that the levels of immune activation were different in two clusters, indicating that pyroptosis could be involved in defining the immunological microenvironment of MM [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations